Reproductive traits of the European catfish, Silurus glanis, during the early stages of invasion - Gkenas, C. (2025)
In recent decades, the European catfish Silurus glanis has spread across Europe and elsewhere, significantly impacting the native fauna of the recipient ecosystems. Studies on its reproductive traits from its non-native range are limited, although this is a critical step in developing effective management plans. Here, we explore the reproductive characteristics of invasive European catfish populations in the Lower River Tagus in Portugal, focusing on its sex ratio, size at maturity, spawning period, fecundity and oocyte diameter. European catfish were collected monthly by electrofishing, gill nets, baited hooks, and professional fishermen from January 2022 to November 2023. A total of 217 females, 156 males and 301 immature fish were analysed. The female-to-male sex ratio was 1.4 : 1, with females and males reaching size at first maturity (TL50) at 72.9 and 68.8 cm total length, respectively. The spawning season was protracted, from February to June, showing asynchronous oocyte development patterns. The absolute fecundity was positively correlated with total length and total weight and ranged from 8,364 to 319,000 oocytes. Relative fecundity varied from 4.39 to 23.53 oocytes, with the mean diameter of the matured oocytes ranging from 1.50 to 3.21 mm. The results obtained in this study enhance our understanding of the reproductive biology of invasive species and can contribute to the development of effective management strategies, such as population control and density- dependent fecundity strategies.